The effects of salt, particle and pore size on the process of carbon dioxide hydrate formation: A critical review - Ghaedi, H. (American Institute of Physics Inc., 2016)
Hydration is an alternative method for CO2 capture. In doing so, some researchers use porous media on an experimental scale. This paper tries to gather the researches on the formation of CO2 hydrate in different types of porous media such as silica sand, quartz sand, Toyoura, pumice, and fire hardened red clay. This review has attempted to examine the effects of salt and particle sizes as two major factors on the induction time, water to hydrate conversion, gas uptake (or gas consumption), and the rate of CO2 hydrate formation. By performing a critical assessment of previous research works, it was observed that the figure for the gas uptake (or gas consumption) and water to hydrate conversion in porous media was decreased by increasing the particle size provided that the pore size was constant. Although, salt can play a role in hydrate formation as the thermodynamic inhibitor, the results show that salt can be regarded as the kinetic growth inhibitor and kinetic promoter. Because of the fact that the gas uptake in seawater is lower than pure water at the end of experiment, the salt can act as a kinetic growth inhibitor. However, since gas uptake (after the nucleation period and for a short period) and the initial rate of hydrate formation in saline water were more than that of pure water, salt can play a promoter role in the kinetic reaction, too. Besides these, in the case of pure water and within a certain particle size, the amount of the hydrate formation rate has been seen to be greater in smaller particles (provided that the pore size is constant), however this has not been observed for seawater. Â© 2016 Author(s).